1986
DOI: 10.1109/irps.1986.362104
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration in Titanium Doped Aluminum Alloys

Abstract: Homogeneous f iLms of titanium-doped aluminum and aluminum-l%siLicon were evaluated for possible application as interconnects in integrated circuits.Titanium concentration was systemnatically varied in the range of 0 to 1.2 wt.%. Electromigration behavior was studied for each film composition as a function of temperature. Significant differences were found between the binary and ternary alloys, corresponding to differences in the film microstructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…5, it has been reported that for small concentrations of Ti doping, electromigration lifetime of Al films is improved dramatically by about two orders of magnitude. But the Ti doping effect on electromigration lifetime turns around and becomes detrimental when the Ti concentration is further increased above a limit at around 0.8 wt%.…”
Section: Discussionmentioning
confidence: 99%
“…5, it has been reported that for small concentrations of Ti doping, electromigration lifetime of Al films is improved dramatically by about two orders of magnitude. But the Ti doping effect on electromigration lifetime turns around and becomes detrimental when the Ti concentration is further increased above a limit at around 0.8 wt%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Ti can diffuse into Al as detected using the RBS measurement, and since Ti is one of the impurities in Al that can enhance its EM lifetime (Fischer and Neppl 1984 Towner, Dirks and Tien 1986;Hosoda, Yagi and Tsuchikawa 1989), the lifetime of TiN/Ti/Al is found to be significantly larger than TiN/Al.…”
Section: Number Of Metallization Levelsmentioning
confidence: 99%